Componential Analysis of Meaning on Lexeme “Look” in English - Ida Cahyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
This study aims to find the difference of components of meaning on lexemes that mean ‘look’ in English. Through semantics study, the analysis employs Nida’s componential analysis of meaning to figure out the distinguished features among lexemes. This is a qualitative research which includes the step of data collection by looking in the lexemes which have meaning “look” form four dictionaries. The data analysis includes filtering the lexemes from dictionaries and analyzing the components of meaning in each lexeme by adding semantic notations to semantic features in each lexeme. The result shows that there are fifteen lexemes which have meaning “look” in English, namely “see, look, watch, stare, gaze, glance, glare, glimpse, gape, behold, peer, peep, peek, blink and wink.” The differences in components of meaning are determined by several semantic features such as the device of seeing (whether using direct eyes or not), the way of seeing, the object and the involved feeling through the process of seeing.